Impact of Correlation of Multimedia Elements with Tablets and Digital Stories in Educational Management - Purwo Haryono (JST (Jurnal Sains dan Teknologi), 2024)
Technological media is an effective teaching method among educators because it is easier and faster to implement. However, the use of interaction features and multimedia elements such as text and images in creating storytelling is still problematic for students and teachers. In addition, the assessment element of storytelling with technology still needs to be improved. The purpose of the study was to analyze the Reliability of Multimedia Elements on Tablets and Digital Story Evaluation and to determine the Correlation of Multimedia Elements on Tablets and Digital Story Evaluation. The research method is a quantitative survey approach. Subjects totaled 67 students, students, teachers, and lecturers. Data collection techniques used instruments developed from indicators of multimedia elements, digital stories, and tablets. The instrument was rated based on a Likert scale from point 1 to point 7. Data analysis techniques using SPSS Version 25.0 with validation test, mean, standard deviation, minimum value, and correlation. Results showed that multimedia, digital stories, and tablets had high reliability and correlation and a positive and significant relationship between all variables in the evaluation. This finding confirms that the elements in multimedia are at level 5 and can be used in an effective learning process. The implication provides an overview for teachers and students to use multimedia as a tool for the learning process actively.